The Burden of Pediatric Asthma - Ferrante, Giuliana; La Grutta, Stefania (Frontiers in Pediatrics, 2018)
Asthma is the most common chronic disease in children, imposing a consistent burden on health system. In recent years, prevalence of asthma symptoms became globally increased in children and adolescents, particularly in Low-Middle Income Countries (LMICs). Host (genetics, atopy) and environmental factors (microbial exposure, exposure to passive smoking and air pollution), seemed to contribute to this trend. The increased prevalence observed in metropolitan areas with respect to rural ones and, overall, in industrialized countries, highlighted the role of air pollution in asthma inception. Asthma accounts for 1.1% of the overall global estimate of “Disability-adjusted life years” (DALYs)/100.000 for all causes. Mortality in children is low and it decreased across Europe over recent years. Children from LMICs particularly suffer a disproportionately higher burden in terms of morbidity and mortality. Global asthma-related costs are high and are usually are classified into direct, indirect and intangible costs. Direct costs account for 50-80% of the total costs. Asthma is one of the main causes of hospitalization which are particularly common in children aged <5 years with a prevalence that has been increased during the last two decades, mostly in LMICs. Indirect costs are usually higher than in older patients, including both school and work-related losses. Intangible costs are unquantifiable, since they are related to impairment of quality of life, limitation of physical activities and study performance. The implementation of strategies aimed at early detect asthma thus providing access to the proper treatment has been shown to effectively reduce the burden of the disease.